Neoliberal policies and Caribbean : from the CBI to the North American Free Trade Agreement. - DIETZ, James L. (1994)
Addresses the major structural and institutional issues and the problems and strategies the Caribbean must address during the 1990s and beyond. Presents the issues within the context of neo-liberalism. Examines the likely impact of regional trading arrangements, like NAFTA, that provide to other countries preferential treatment so far reserved for the CBI nations.